Existentialist Feminism Simone de Beauvoir in Arthur Miller's Novela Fatātun 'Ādiyah - Al Barka, Ahmad Muwaffaq; Basid, Abdul (Universitas Negeri Semarang, 2024)
The study of existentialist feminism is vital in advancing women's lives. This study of feminism was initiated by Simone de Beauvoir, who fought for women's existence in her time. Her theory has also considerably influenced society's views towards women in the realm of feminism. This study aims to identify the basic concepts of existentialist feminism in Arthur Miller’s novella Fatātun ‘Ādiyah, translated into Arabic by Tala’at as-Shayeb, including 1) Otherness, 2) Immanence and Transcendence, and 3) freedom. In addition, it also analyzes the strategies carried out by female characters in the novella to advance their lives, as in the study of existentialist feminism, including 1) women become intellectuals, 2) women can work, 3) women can achieve social transformation, and 4) women can reject their Otherness. This descriptive qualitative research uses reading and recording techniques in data collection and analysis using the Miles and Huberman analysis technique. The results of this study show that women can leave the status of Objects and the limits of their Immanence and achieve freedom and Subject status for themselves. Thus, female characters will become independent and achieve gender equality and freedom for themselves. The benefit of this research is that it provides insights for society to respect each other more and consider everything equal without discriminating, especially in the context of gender.